Zweierlei Homophilie: Wendy Hui Kyong Chun und Leo Bersani - Althoff, Sebastian (Mimesis Expanded: Die Ausweitung der mimetischen Zone)

Musterbildungen. Ein alternativer Zugang zur Fernsehgeschichte: Über Lynn Spigels TV Snapshots – An Archive of Everyday Life - Miggelbrink, Monique (Cargo H. 56)

The DaimlerChrysler takeover failure revisited from a varieties-of-capitalism perspective - Riach, John Rankin Wood; Schneider, Martin (Cross Cultural and Strategic Management)
Purpose The purpose of this paper is to revisit the disastrous DaimlerChrysler AG takeover episode from 1998 to 2007 in order to arrive at a more comprehensive explanation of this and other merger and takeover failures based on institutional theory. Design/methodology/approach The case study is based on various secondary sources of information and on the insights that one of the authors gained from working for 14 years in various positions for Daimler-Benz and DaimlerChrysler. Findings DaimlerChrysler failed because top management made mistakes in trying to globalize the company. They were unable to realize possible synergies between the two companies, which brought complementary resources into the merger. Furthermore, they did not account for the institutional embeddedness of strategies when they adopted lean production globally, diffused the production system developed in Germany to other parts of the world and tried to implement a global stock enlisted in New York and Frankfurt. The underlying theoretical framework is relevant for other merger and acquisition cases. It features institutional embeddedness, path dependency and institutional arbitrage. Originality/value The paper develops an institutional perspective on DaimlerChrysler and on cross-border merger and acquisition failure more generally. The perspective is organized around the varieties-of-capitalism approach. This contribution is important because there is increasing dissatisfaction with the dominant explanation of cross-border merger and acquisition failure, which is based on the allegedly failed management of culture “clashes.”
Keywords: Organizational Behavior and Human Resource Management; Strategy and Management; Sociology and Political Science; Cultural Studies; Business and International Management

Dequantizing the Quantum Singular Value Transformation: Hardness and Applications to Quantum Chemistry and the Quantum PCP Conjecture - Gharibian, Sevag; Gall, François Le (Proceedings of the 54th ACM Symposium on Theory of Computing (STOC))
The Quantum Singular Value Transformation (QSVT) is a recent technique that gives a unified framework to describe most quantum algorithms discovered so far, and may lead to the development of novel quantum algorithms. In this paper we investigate the hardness of classically simulating the QSVT. A recent result by Chia, Gily\'en, Li, Lin, Tang and Wang (STOC 2020) showed that the QSVT can be efficiently "dequantized" for low-rank matrices, and discussed its implication to quantum machine learning. In this work, motivated by establishing the superiority of quantum algorithms for quantum chemistry and making progress on the quantum PCP conjecture, we focus on the other main class of matrices considered in applications of the QSVT, sparse matrices. We first show how to efficiently "dequantize", with arbitrarily small constant precision, the QSVT associated with a low-degree polynomial. We apply this technique to design classical algorithms that estimate, with constant precision, the singular values of a sparse matrix. We show in particular that a central computational problem considered by quantum algorithms for quantum chemistry (estimating the ground state energy of a local Hamiltonian when given, as an additional input, a state sufficiently close to the ground state) can be solved efficiently with constant precision on a classical computer. As a complementary result, we prove that with inverse-polynomial precision, the same problem becomes BQP-complete. This gives theoretical evidence for the superiority of quantum algorithms for chemistry, and strongly suggests that said superiority stems from the improved precision achievable in the quantum setting. We also discuss how this dequantization technique may help make progress on the central quantum PCP conjecture.

Ich. Das bin ich! Zugehörigkeit, Freundschaft und Familie. Zyklus 2 - Tenberge, Claudia; von Braunmühl, Susanne

Lebensformen, Welt, Gesellschaft. Alltagsleben, Gemeinschaft und Feste. Zyklus 2. - Tenberge, Claudia; von Braunmühl, Susanne

Ich und die anderen. Zugehörigkeit, Freundschaft und Familie. Zyklus 2. - Tenberge, Claudia; von Braunmühl, Susanne

Kultur und Kommunikation. Religion, Sprache und Verständigung. Zyklus 3. - Tenberge, Claudia; von Braunmühl, Susanne

Große Fragen. Welt und Wahrheit. Leben und Tod. Zyklus 3. - Tenberge, Claudia; von Braunmühl, Susanne

Lebensformen, Welt, Gesellschaft. Normen und Werte - Religionen und Kulturen. Zyklus 3. - Tenberge, Claudia; von Braunmühl, Susanne

Mensch, Natur, Technik. Lebenswelt, Information und Sprache. Zyklus 3. - Tenberge, Claudia; von Braunmühl, Susanne

Neural Network-Based Demand-Side Management in a Stand-Alone Solar PV-Battery Microgrid Using Load-Shifting and Peak-Clipping - Philipo, Godiana Hagile; Kakande, Josephine Nakato; Krauter, Stefan (Energies)
Due to failures or even the absence of an electricity grid, microgrid systems are becoming popular solutions for electrifying African rural communities. However, they are heavily stressed and complex to control due to their intermittency and demand growth. Demand side management (DSM) serves as an option to increase the level of flexibility on the demand side by scheduling users’ consumption patterns profiles in response to supply. This paper proposes a demand-side management strategy based on load shifting and peak clipping. The proposed approach was modelled in a MATLAB/Simulink R2021a environment and was optimized using the artificial neural network (ANN) algorithm. Simulations were carried out to test the model’s efficacy in a stand-alone PV-battery microgrid in East Africa. The proposed algorithm reduces the peak demand, smoothing the load profile to the desired level, and improves the system’s peak to average ratio (PAR). The presence of deferrable loads has been considered to bring more flexible demand-side management. Results promise decreases in peak demand and peak to average ratio of about 31.2% and 7.5% through peak clipping. In addition, load shifting promises more flexibility to customers.
Keywords: Energy (miscellaneous); Energy Engineering and Power Technology; Renewable Energy; Sustainability and the Environment; Electrical and Electronic Engineering; Control and Optimization; Engineering (miscellaneous); Building and Construction

Turn all the lights off: Bright- and dark-field second-harmonic microscopy to select contrast mechanisms for ferroelectric domain walls - Hegarty, Peter A.; Beccard, Henrik; Eng, Lukas M.; Rüsing, Michael (Journal of Applied Physics)
Recent analyses by polarization resolved second-harmonic (SH) microscopy have demonstrated that ferroelectric (FE) domain walls (DWs) can possess non-Ising wall characteristics and topological nature. These analyses rely on locally analyzing the properties, directionality, and magnitude of the second-order nonlinear tensor. However, when inspecting FE DWs with SH microscopy, a manifold of different effects may contribute to the observed signal difference between domains and DWs, i.e., far-field interference, Čerenkov-type phase-matching (CSHG), and changes in the aforementioned local nonlinear optical properties. They all might be present at the same time and, therefore, require careful interpretation and separation. In this work, we demonstrate how the particularly strong Čerenkov-type contrast can selectively be blocked using dark- and bright-field SH microscopy. Based on this approach, we show that other contrast mechanisms emerge that were previously overlayed by CSHG but can now be readily selected through the appropriate experimental geometry. Using the methods presented, we show that the strength of the CSHG contrast compared to the other mechanisms is approximately 22 times higher. This work lays the foundation for the in-depth analysis of FE DW topologies by SH microscopy.
Keywords: General Physics and Astronomy

High-speed hyperspectral imaging of ferroelectric domain walls using broadband coherent anti-Stokes Raman scattering - Reitzig, Sven; Hempel, Franz; Ratzenberger, Julius; Hegarty, Peter A.; Amber, Zeeshan H.; Buschbeck, Robin; Rüsing, Michael; Eng, Lukas M. (Applied Physics Letters)
Spontaneous Raman spectroscopy (SR) is a versatile method for analysis and visualization of ferroelectric crystal structures, including domain walls. Nevertheless, the necessary acquisition time makes SR impractical for in situ analysis and large scale imaging. In this work, we introduce broadband coherent anti-Stokes Raman spectroscopy (B-CARS) as a high-speed alternative to conventional Raman techniques and demonstrate its benefits for ferroelectric domain wall analysis. Using the example of poled lithium niobate, we compare the spectral output of both techniques in terms of domain wall signatures and imaging capabilities. We extract the Raman-like resonant part of the coherent anti-Stokes signal via a Kramers–Kronig-based phase retrieval algorithm and compare the raw and phase-retrieved signals to SR characteristics. Finally, we propose a mechanism for the observed domain wall signal strength that resembles a Čerenkov-like behavior, in close analogy to domain wall signatures obtained by second-harmonic generation imaging. We, thus, lay here the foundations for future investigations on other poled ferroelectric crystals using B-CARS.
Keywords: Physics and Astronomy (miscellaneous)

Tuning domain wall conductivity in bulk lithium niobate by uniaxial stress - Singh, Ekta; Beccard, Henrik; Amber, Zeeshan H.; Ratzenberger, Julius; Hicks, Clifford W.; Rüsing, Michael; Eng, Lukas M. (Physical Review B)
Conductive domain walls (DWs) in insulating ferroelectrics have recently attracted considerable attention due to their unique topological, optical, and electronic properties, and offer potential applications such as in memory devices or rewritable circuitry. The electronic properties of DWs can be tuned by the application of strain, hence controlling the charge carrier density at DWs. In this paper, we study the influence of uniaxial stress on the conductivity of DWs in the bulk single crystal lithium niobate (LiNbO3). Using conductive atomic force microscopy, we observe a large asymmetry in the conductivity of DWs, where only negatively screened walls, so called head-to-head DWs, are becoming increasingly conductive, while positively screened, tail-to-tails DWs, show a decrease in conductivity. This asymmetry of DW conductivity agrees with our theoretical model based on the piezoelectric effect. In addition, we observed that the current in the DW increases up to an order of magnitude for smaller compressive stresses of 100 MPa. This response of DWs remained intact for multiple stress cycles over two months, opening a path for future applications.

Nanoscale Conductive Sheets in Ferroelectric BaTiO3: Large Hall Electron Mobilities at Head-to-Head Domain Walls - Beccard, Henrik; Kirbus, Benjamin; Beyreuther, Elke; Rüsing, Michael; Bednyakov, Petr; Hlinka, Jiří; Eng, Lukas M. (ACS Applied Nano Materials)
Strongly charged head-to-head domain walls that are purposely engineered along the [110] crystallographic orientation into ferroelectric BaTiO3 single crystals have been proposed as intrinsically nanoscaled two-dimensional electron gases (2DEGs) because of their significant conductivity. Here, we quantify these 2DEG properties through dedicated Hall transport measurements in van der Pauw 4-point geometry, finding the electron mobility to reach around 400 cm2 (V s)^{−1}, while the two-dimensional charge density amounts to 7 × 103 cm^{–2}. We underline the necessity to take into account the thermal and geometrical misalignment offset voltages by evaluating the Hall resistance under magnetic field sweeps; otherwise, errors of several hundred percent in the derived transport parameters can occur.
Keywords: General Materials Science

Investigation of ferroelectric domain walls in periodically-poled LiNbO3 single crystals by polarization-sensitive optical coherence tomography - Golde, Jonas; Rüsing, Michael; Kindler, Richard; Steuer, Svea; Rix, Jan; Eng, Lukas M.; Koch, Edmund (Optical Components and Materials XIX)

Nonlinear optical interactions in focused beams and nanosized structures - Amber, Zeeshan H.; Spychala, Kai J.; Eng, Lukas M.; Rüsing, Michael (Journal of Applied Physics)
Thin-film materials from μm thickness down to single-atomic-layered 2D materials play a central role in many novel electronic and optical applications. Coherent, nonlinear optical (NLO) μ-spectroscopy offers insight into the local thickness, stacking order, symmetry, or electronic and vibrational properties. Thin films and 2D materials are usually supported on multi-layered substrates leading to (multi-)reflections, interference, or phase jumps at interfaces during μ-spectroscopy, which all can make the interpretation of experiments particularly challenging. The disentanglement of the influence parameters can be achieved via rigorous theoretical analysis. In this work, we compare two self-developed modeling approaches, a semi-analytical and a fully vectorial model, to experiments carried out in thin-film geometry for two archetypal NLO processes, second-harmonic and third-harmonic generation. In particular, we demonstrate that thin-film interference and phase matching do heavily influence the signal strength. Furthermore, we work out key differences between three and four photon processes, such as the role of the Gouy-phase shift and the focal position. Last, we can show that a relatively simple semi-analytical model, despite its limitations, is able to accurately describe experiments at a significantly lower computational cost as compared to a full vectorial modeling. This study lays the groundwork for performing quantitative NLO μ-spectroscopy on thin films and 2D materials, as it identifies and quantifies the impact of the corresponding sample and setup parameters on the NLO signal, in order to distinguish them from genuine material properties.<
Keywords: General Physics and Astronomy

Ba(BO2OH) – A Monoprotonated Monoborate from Hydroflux Showing Intense Second Harmonic Generation - Li, Yuxi; Hegarty, Peter A.; Rüsing, Michael; Eng, Lukas M.; Ruck, Michael (Zeitschrift für anorganische und allgemeine Chemie)
Abstract Pure samples of colorless, air‐stable Ba(BO 2 OH) crystals were obtained from Ba(NO 3 ) 2 and H 3 BO 3 under the ultra‐alkaline conditions of a KOH hydroflux at about 250 °C. The product formation depends on the water‐base molar ratio and the molar ratio of the starting materials. B(OH) 3 acts as a proton donor (Brønsted acid) rather than a hydroxide acceptor (Lewis acid). Ba(BO 2 OH) crystallizes in the non‐centrosymmetric orthorhombic space group P 2 1 2 1 2 1 . Hydrogen bonds connect the almost planar (BO 2 OH) 2− anions, which are isostructural to HCO 3 − , into a syndiotactic chain. IR and Raman spectroscopy confirm the presence of hydroxide groups, which are involved in weak hydrogen bonds. Upon heating in air to about 450 °C, Ba(BO 2 OH) dehydrates to Ba 2 B 2 O 5 . Moreover, the non‐centrosymmetric structure of Ba(BO 2 OH) crystals was verified with power‐dependent confocal Second Harmonic Generation (SHG) microscopy indicating large conversion efficiencies in ambient atmosphere.
Keywords: Inorganic Chemistry

Tuning the Čerenkov second harmonic contrast from ferroelectric domain walls via anomalous dispersion - Hegarty, Peter A.; Eng, Lukas M.; Rüsing, Michael (Journal of Applied Physics)
Second harmonic (SH) microscopy represents a powerful tool for the investigation of crystalline systems, such as ferroelectrics and their domain walls (DWs). Under the condition of normal dispersion, i.e., the refractive index at the SH wavelength is larger as compared to the refractive index at the fundamental wavelength, n(2ω)>n(ω), bulk crystals will generate no SH signal. Should the bulk, however, contain DWs, an appreciable SH signal will still be detectable at the location of DWs stemming from the Čerenkov mechanism. In this work, we demonstrate both how SH signals are generated in bulk media and how the Čerenkov mechanism can be inhibited by using anomalous dispersion, i.e., n(ω)<n(2ω). This allows us to quantitatively estimate the relative strength of the Čerenkov compared to other SH contrast mechanisms in DWs, such as the interference contrast. The results are in agreement with previous experiments based on the geometric separation of the signals. Due to the observed, strong Čerenkov contrast, such signal contributions may not be neglected in polarimetry studies of ferroelectric DWs in the future.
Keywords: General Physics and Astronomy

Im Nationalsozialismus: Praktiken – Kommunikation – Diskurse. Teil 1
Keywords: Kommunikationsgeschichte

Biographisches Erzählen und digitale Medien - Schuster, Britt-Marie (Handbuch Biographie. Methoden, Traditionen, Theorien)
Keywords: Historische Medienlinguistik

Gegengemeinschaften bilden: Ein Beitrag zur linguistischen Geschichtsschreibung des Widerstands (1933–1945) - Schuster, Britt-Marie (Sprache in Politik und Gesellschaft. Perspektiven und Zugänge. Jahrbuch des Instituts für Deutsche Sprache 2021)
Keywords: Kommunikationsgeschichte

Äußerungen formelhaft kommentieren: Bauernkomödien als Quelle historischer Idiomatik - Schuster, Britt-Marie; Georgi, Christopher (Bauernkomödien des 17. Jahrhunderts als sprachhistorische Quellen)
Keywords: Sprachliche Formelhaftigkeit/-Musterhaftigkeit

Brief - Dang-Anh, Mark; Scholl, Stefan; Schuster, Britt-Marie (Im Nationalsozialismus)
Keywords: Kommunikationsgeschichte

Flugblatt – Flugschrift - Schuster, Britt-Marie (Im Nationalsozialismus)
Keywords: Kommunikationsgeschichte

From Pure Art to Sheer Luxury: Magazines as Ornamental Constellations and the Emergence of Aesthetic Capitalism in the Early Twentieth Century - Gretz, Daniela; Krause, Marcus (Periodical Formats in the Market)
The concept of ‘ornamental constellations’ introduced in the following article highlights the structural relationships of decorative elements and miscellaneous content in magazines and the importance of the reader’s perspective for their interpretation. ‘Ornamental constellations’ are considered one of the most important media devices of emerging aesthetic capitalism, as they produce economies of attention and affect and establish a visual connection between the basic concept of a magazine, its individual contributions, and the readership addressed, thus promoting a specific aesthetic lifestyle. Their respective staging value is illustrated by analysing two complementary magazines and their constellation techniques: the elitist art magazine Blätter für die Kunst with its ‘strategic arrangement’ of literary and programmatic contributions and the creation of ‘resonances’ between them and the popular sports and society magazine Sport im Bild with its hybridizing flow of texts, images, and advertisements. Despite all the differences, it becomes clear that these are two quite compatible projects within the framework of an emerging aesthetic capitalism: whereas the Blätter für die Kunst staged and materialized the idea of pure art as an exclusive aesthetic lifestyle, the Sport im Bild made the desired aesthetic way of life also attainable by non-artists (with enough money) by associating it with the idea of an aesthetic capitalism.
Keywords: General Medicine

Introduction: English Linguistics, Learners and the Classroom - Hahn, Charlotte Anna; Mindt, Ilka (Anglistik)
Keywords: General Medicine

Aufwärtsstreben als Niedergang oder Variationen des Immergleichen. Zur Ästhetik der Serialität in Gottfried Kellers "Martin Salander" in der "Deutschen Rundschau" - Gretz, Daniela (Kellers Erzählen)

Medieneffekte und -reflexionen im Erstdruck von Theodor Fontanes "Stechlin" in "Über Land und Meer" - Gretz, Daniela (Fontanes Medien)

Ein Blick auf: Verstetigung und Transfer im Bundesprogramm „Kita-Einstieg: Brücken bauen in frühe Bildung“ - Albers, Timm; Hoeft, Maike; Abendroth, Sonja; Meusel, Sarah

Erkenntnisse zu Verstetigung und Transfer im Bundesprogramm "Kita-Einstieg: Brücken bauen in frühe Bildung" - Abendroth, Sonja; Hoeft, Maike; Meusel, Sarah

'Surprised, Shocked, Worried': User Reactions to Facebook Data Collection from Third Parties - Arias Cabarcos, Patricia; Khalili, Saina; Strufe, Thorsten (arXiv:2209.08048)
Data collection and aggregation by online services happens to an extent that is often beyond awareness and comprehension of its users. Transparency tools become crucial to inform people, though it is unclear how well they work. To investigate this matter, we conducted a user study focusing on Facebook, which has recently released the "Off-Facebook Activity" transparency dashboard that informs about personal data collection from third parties. We exposed a group of n = 100 participants to the dashboard and surveyed their level of awareness and reactions to understand how transparency impacts users' privacy attitudes and intended behavior. Our participants were surprised about the massive amount of collected data, became significantly less comfortable with data collection, and more likely to take protective measures. Collaterally, we observed that current consent schemes are inadequate. Based on the survey findings, we make recommendations for more usable transparency and highlight the need to raise awareness about transparency tools and to provide easily actionable privacy controls.

(Semi-)Automatische Kommentarmoderation zur Erhaltung Konstruktiver Diskurse - Niemann, Marco; Assenmacher, Dennis; Brunk, Jens; Riehle, Dennis Maximilian; Becker, Jörg; Trautmann, Heike (Hate Speech — Definitionen, Ausprägungen, Lösungen)

Textual One-Pass Stream Clustering with Automated Distance Threshold Adaption - Assenmacher, D; Trautmann, Heike (Intelligent Information and Database Systems)

Benchmarking Crisis in Social Media Analytics: A Solution for the Data-Sharing Problem - Assenmacher, Dennis; Weber, Derek; Preuss, Mike; Valdez, André Calero; Bradshaw, Alison; Ross, Björn; Cresci, Stefano; Trautmann, Heike; Neumann, Frank; Grimme, Christian (Social Science Computer Review)
Computational social science uses computational and statistical methods in order to evaluate social interaction. The public availability of data sets is thus a necessary precondition for reliable and replicable research. These data allow researchers to benchmark the computational methods they develop, test the generalizability of their findings, and build confidence in their results. When social media data are concerned, data sharing is often restricted for legal or privacy reasons, which makes the comparison of methods and the replicability of research results infeasible. Social media analytics research, consequently, faces an integrity crisis. How is it possible to create trust in computational or statistical analyses, when they cannot be validated by third parties? In this work, we explore this well-known, yet little discussed, problem for social media analytics. We investigate how this problem can be solved by looking at related computational research areas. Moreover, we propose and implement a prototype to address the problem in the form of a new evaluation framework that enables the comparison of algorithms without the need to exchange data directly, while maintaining flexibility for the algorithm design.

Auf Deutsch gesagt: eine Wortschatzkunde für Deutsch als Fremdsprache - Kilsbach, Sebastian; Augst, Gerhard

EFFECT OF SHREDDING PARAMETERS ON THE FORMATION OF AIRBORNE FIBER DUST DURING MECHANICAL RECYCLING OF FIBER-REINFORCED THERMOPLASTICS - Hopp, Matthias; Tölle, Lisa (Proceedings of the 20th European Conference on Composite Materials)

Zero-Sequence Voltage Reduces DC-Link Capacitor Demand in Cascaded H-Bridge Converters for Large-Scale Electrolyzers by 40% - Unruh, Roland; Schafmeister, Frank; Böcker, Joachim (24th European Conference on Power Electronics and Applications (EPE'22 ECCE Europe))
Cascaded H-bridge Converters (CHBs) are a promising solution in converting power from a three-phase medium voltage of 6.6 kV...30 kV to a lower DC-voltage in the range of 100 V...1 kV to provide pure DC power to applications such as electrolyzers for hydrogen generation, data centers with a DC power distribution and DC microgrids. CHBs can be interpreted as modular multilevel converters with an isolated DC-DC output stage per module, require a large DC-link capacitor for each module to handle the second harmonic voltage ripple caused by the fluctuating input power within a fundamental grid period. Without a zero-sequence voltage injection, star-connected CHBs are operated with approximately sinusoidal arm voltages and currents. The floating star point potential enables to utilize different zero-sequence voltage injection techniques such as a third-harmonic injection with 1/6 of the grid voltage amplitude or a Min-Max voltage injection. Both well-known methods have the advantage to reduce the peak arm voltage and thereby the number of required modules by 13.4 % (to √ 3 2). This paper proves analytically that the third-harmonic injection with 1/6 of the grid voltage amplitude reduces the second harmonic voltage ripple by only 15.1 % compared to no-voltage injection for unity power factor operation and balanced grid voltages. Then it is shown, that the Min-Max injection has the often overlooked advantage of reducing the second harmonic voltage ripple by even 18.8 %. By applying the here proposed zero-sequence voltage injection in saturation modulation, the second harmonic voltage ripple of the DC-link capacitors is reduced by even 24.3 %, while still requiring the same number of modules as the Min-Max injection. For a realistic number of reserve modules, the overall energy ripple in the DC-link capacitors is reduced by 40 %.
Keywords: Cascaded H-Bridge; Solid-State Transformer; Zero sequence voltage; Third harmonic injection; Capacitor voltage ripple

Neural Network Based Carrier Frequency Offset Estimation From Speech Transmitted Over High Frequency Channels - Heitkämper, Jens; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (Proceedings of the 30th European Signal Processing Conference (EUSIPCO))
The intelligibility of demodulated audio signals from analog high frequency transmissions, e.g., using single-sideband (SSB) modulation, can be severely degraded by channel distortions and/or a mismatch between modulation and demodulation carrier frequency. In this work a neural network (NN)-based approach for carrier frequency offset (CFO) estimation from demodulated SSB signals is proposed, whereby a task specific architecture is presented. Additionally, a simulation framework for SSB signals is introduced and utilized for training the NNs. The CFO estimator is combined with a speech enhancement network to investigate its influence on the enhancement performance. The NN-based system is compared to a recently proposed pitch tracking based approach on publicly available data from real high frequency transmissions. Experiments show that the NN exhibits good CFO estimation properties and results in significant improvements in speech intelligibility, especially when combined with a noise reduction network.

Data-driven Time Synchronization in Wireless Multimedia Networks - Afifi, Haitham; Karl, Holger; Gburrek, Tobias; Schmalenstroeer, Joerg (2022 International Wireless Communications and Mobile Computing (IWCMC))

Parental involvement and Children's internet uses - Relationship with parental role construction, self-efficacy, internet skills, and parental instruction - Gruchel, Nicole; Kurock, Ricarda; Bonanati, Sabrina; Buhl, Heike M. (Computers & Education)
Internet use is significant in the everyday lives of children and can be distinguished into different uses (e.g., entertainment-related, informative or school-related). When considering the literature on internet inquiries, the family as an informal place of learning is of particular importance. Although some predictors within the family (e.g., structural factors) are widely researched, comprehensive results on the influence of parental involvement, especially parental instruction as a form of parental support during information-related internet activities, on different internet uses are still lacking. Therefore, the study investigates (1) the relationship of parental role construction, self-efficacy, internet skills, and parental instruction in information-related internet use perceived by parents and children and (2) the relationship of parental role construction, self-efficacy, internet skills, parental instruction, and children's internet uses at home (entertainment-related, practical and school-or-learning-related). The mediation effects of parental instruction were also tested. A paper-and-pencil questionnaire was answered by 361 German children and their parents. Structural equation modeling was applied to answer the research questions. We observed that children's perceived parental instruction was positively associated with children's practical and school-or-learning-related internet use. Parents' motivational factors were the strongest predictors for parents' perceived parental instruction The findings have significant implications for research and practice on how parents can be more active in fulfilling their role as supporters for children's internet use.

Voluntary Submission and the ʻPolitics of Truth’: Nietzsche and Foucault on the Danger of the Fully Normalised ‘Last Human’ - Corall, Niklas (Nietzsche and the Politics of Difference)

Warum Personalführung in Start-ups anders funktioniert - Hubner-Benz, Sylvia

Creating social and environmental value through integrated thinking: International evidence - Reimsbach, Daniel; Braam, Geert (Business Strategy and the Environment)
Abstract Integrated thinking (IT) is a managerial mindset increasingly discussed in the context of value creation. Through the lens of systems theory, this study examines how the degree to which IT is embedded in a firm's strategy and day‐to‐day business processes is associated with the firm's social and environmental value creation. Using a broad international dataset, we find strong evidence that our measure of IT is positively related to a firm's sustainability performance (SP), which we use to operationalize social and environmental value creation (or erosion). Our results also reveal that the increase in a firm's SP might come at the cost of a short‐term decrease in financial performance (FP). We find no indication, however, that IT induces a trade‐off between SP and long‐term FP. Integrated thinking appears to stipulate long‐term financial value creation instead. We further explore moderating factors within the organizational and institutional context of our sample firms and highlight implications for society, corporate practice, and policymaking.
Keywords: Management; Monitoring; Policy and Law; Strategy and Management; Geography; Planning and Development; Business and International Management

New aspects of modeling and operation of nitrous gas absorption in packed columns - Mackowiak, Jan F.; Franke, Patrick; Chromik, Reiner; Mackowiak, Jerzy (Proceedings of the 12th International Conference Distillation & Absorption Toulouse)

Eye-Tracking Studie zu Textaufgaben in Klasse 5: Bemerken und Interpretieren syntaktischer Strukturen - Dröse, Jennifer; Neugebauer, P.; Delucchi Danhier, R.; Mertins, B. (Eye-Tracking in der Mathematik- und Naturwissenschaftsdidaktik. Forschung und Praxis)

Teacher expertise for fostering at-risk students’ understanding of basic concepts: conceptual model and evidence for growth - Prediger, S.; Dröse, Jennifer; Stahnke, R.; Ademmer, C. (Journal of Mathematics Teacher Education)

Prosepctive teachers‘ diagnostic judgements on students’ under- standing of conditional probabilities - Dröse, Jennifer; Griese, B.; Wessel, Lena (Twelfth Congress of the European Society for Research in Mathematics Education (CERME12))

Weiterentwicklung eines physikdidaktischen Tests zum Online-Assessment - Jordans, Melanie; Zeller, Jannis; Große-Heilmann, Rike Isabel; Riese, Josef (Unsicherheit als Element von naturwissenschaftsbezogenen Bildungsprozessen. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung virtuell 2021)